ON A RESPONSE FUNCTION AND TWO-BODY DENSITY MATRIX OF NUCLEAR MATTER - Mavrommatis, E.; Petraki, M.; Clark, J. W.; Kwong, N. H. (HNPS Advances in Nuclear Physics, 2020)
We present a summary of on-going calculations that address the static and dynamic structure of nuclear matter. Specific projects include (i) evaluation of the density-density response function and corresponding dynamic structure factor, based on the correlated random-phase approximation (CRPA_I) and generalizations of this method, and (ii) low-order variational calculation of the reduced two-body density matrix and corresponding generalized momentum distribution. The numerical applications involve the model interaction V2.